Pengaruh Penambahan Carboxy Methyl Cellulose (CMC) dengan Plasticizer Gliserol terhadap Sifat Fisik Plastik Biodegradable Berbahan Dasar Durian (Durio Zibethinus) - Gusriandi, Dedi; Ratnawulan, Ratnawulan (Lembaga Yasin AlSys, 2025)
Synthetic plastics that are currently widely used pose a threat to the environment as they are non-biodegradable and derived from non-renewable petrochemical sources. The use of plastics has generated hundreds of millions of tons of waste per year globally while the average usage time is less than 25 minutes. Making biodegradable plastics with materials such as starch, gluten, and guar gum is one way to overcome the problems of using synthetic plastics. One of the materials that can be used as biodegradable is durian seed starch. The purpose of this study was to determine the effect of the addition of carboxymethyl cellulose (CMC) concentration on the physical characteristics of durian seed-based biodegradable plastics. This research is experimental, with the concentration of carboxymethyl cellulose (CMC) added as an independent variable and the mass of starch, sorbitol plasticizer, distilled water, and sample thickness of 0.24 mm as control variables. The tests carried out include tensile strength and elongation tests as well as water resistance tests and biodegradation tests. This research was conducted by varying CMC, namely 15%, 20%, 25%, 30%, and 35% (w/w starch) using 5 grams of durian seed starch as the mixing material and 3 ml of sorbitol plasticizer as the plasticizer concentration. This study showed that the addition of starch with CMC concentration up to 35% w/w had an impact on the tensile strength and elongation values of the plastic. The weight loss percentage of the biodegradable polymer increased when CMC concentration was added, and the water resistance level decreased when CMC concentration was added in amounts up to 35% w/w starch.